Do Real Estate Contingency Clauses Affect Selling Price and Time-on-the-Market? - Bruce L. Gordon; Michael J. Seiler; Ralph Siebert; Daniel T. Winkler (Center for Economic Studies and ifo Institute (CESifo), 2022)
Real estate contracts often contain a wide variety of contingency clauses. These third-party approvals are often outside the seller's control and can lengthen the-time-on-the-market (TOM) and reduce the surety of close. To compensate for these undesirable attributes, buyers typically offer higher purchase prices. This study examines the factors affecting contract contingencies and the effect of contract contingencies on TOM and selling price. Using transactions from Miami-Dade County in south Florida, we find that the presence of contingency clauses is significantly related to market conditions, TOM, list price premiums, distressed transactions, brokerage characteristics, home occupancy status, size, and age. Contingency clauses have differential effects on price premia that range from -3.7% to +2.2%. However, when considering TOM, contingency clauses have significant price premia ranging from -3.3% to +2.4%.
Keywords: R30; R31; L85; 330; contingency clauses; price premia; real estate contracts; time-on-the-market; selling price